Synthesis of copper nanoparticles by electroreduction process - Mohan, Raja; J, Subha; Ali, Fathilah; Ryu, Sung Hun (Taylor & Francis, 2008)
Copper nanoparticles have been prepared by electro-reduction process using plating bath containing homogeneously acidified copper sulphate solution. The nanoparticles are formed as spongy layers of ball structures on the plating electrode. The spongy layers of copper can be easily separated to give fine particles. Structural characterizations are done by using X-ray diffraction, X-ray photoelectron spectroscopy, and ultraviolet-visible spectroscopy. Morphological characterizations are done by scanning electron microscope (SEM) and transmission electron microscope (TEM).